Answer:
43.75%
Step-by-step explanation:
Answer:
x ≈ ±20.086/√(t - 1)
Step-by-step explanation:
ln(t - 1) + ln(x²) = 6
Recall that lnu + lnv = ln(uv). Then
ln(t - 1) + ln(x²) = ln[(t-1)x²] = 6
Take the natural antilogarithm of each side
(t - 1)x² = e⁶
Divide each side by t - 1
x² = e⁶/(t-1)
Take the square root of each side
x = ±e³/√(t - 1)
x ≈ ±20.086/√(t - 1)
Answer:
Step-by-step explanation:
Surface area of objects with flat surfaces like this is simply the area of each surface added together, so let's get to work.
Both have 6 faces, so we will be adding six values together for each.
Container A:
Hopefully you can imagine the six different faces. It's kinda like a cereal box.
The front and back of a cereal box have the same area, as do the two sides and the top and bottom, so that makes it a little easier.
Front and Back: 28 * 36 = 1008
Sides: 36*6 = 216
Top and Bottom: 6*28 = 168
Let me know if you don't understand how I did any of that. Anyway, since there is a matching face for each we add them all together twice.
1008*2 + 216*2 + 168*2 = 2784 in^2
Container B has a similar setup, I won't write out everything like I did unless you want me to work it out with you.
2(16*12+16*22+22*12) = 1616 in^2
So since Container A has a surface area of 2784 and Container B has a surface area of 1616 it's obvious container A has a larger surface area
Answer:
the answer is C I'm studying this right now
Answer:
53.2
Step-by-step explanation: